VD_FINDINFO HC / 2010 / 234 vom 8. Juli 2010 - VD Tribunal cantonal (2010)
DOL ÉVENTUEL, LÉSION CORPORELLE PAR NÉGLIGENCE, NÉGLIGENCE, LÉGITIME DÉFENSE, EXCÈS | 12 al. 2 CP, 12 al. 3 CP, 125 al. 1 CP, 16 CP, 411 let. h CPP, 411 let. i CPP, 411 let. j CPP, 415 CPP